Exploring AI-based Engvit Applications for Vocational High School Students - Dewa Putu Ramendra; Made Dharma Susena Suyasa; I Luh Meiyana Ariss Susanti (Universitas Pendidikan Ganesha, 2025)
English language learning in vocational high schools (SMK) still faces various challenges, particularly in providing instructional media that accommodate diverse student learning styles and offer contextual, practical learning experiences. Conventional methods often fall short in simulating real-world situations, thus hindering the development of students’ communication skills. This study aims to develop and evaluate the feasibility of Engvit, a learning application based on Artificial Intelligence (AI) and Virtual Tour technology, designed to enhance vocational students’ English skills in an immersive and industry-relevant manner. This research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques included expert validation, practicality questionnaires from teachers and students, and documentation. The validation results showed that Engvit received scores of 93.5% from language experts, 95.5% from content experts, and 97.0% from media experts, all categorized as highly valid. Practicality tests also yielded excellent results: 95% in individual trials, 96% in small group trials, and 90% from teacher assessments. These findings indicate that Engvit is a feasible, practical, and innovative learning tool capable of addressing the challenges of English language instruction in vocational schools in a more contextual and technologically adaptive way.